Maternal depression and anxiety and fetal-neonatal growth - Pinto, Tiago Miguel (2017)
Maternal depression and anxiety have been found to negatively affect fetal and neonatal growth. However, the independent effects of maternal depression and anxiety on fetal-neonatal growth outcomes and trajectories remain unclear. This study aimed to analyze simultaneously the effects of maternal prenatal depression and anxiety on (1) neonatal growth outcomes, and (2), on fetal-neonatal growth trajectories, from the 2nd trimester of pregnancy to childbirth.